California Democratic Delegation Daily Report - Jesse M. Unruh:::::: (1968)
A "Daily Report" for the California Democratic Delegation outlines convention activities in Chicago, including a Tuesday caucus where Vice President Humphrey and Senators McCarthy and McGovern will jointly address the delegation and answer questions. It provides security instructions for attendance, transportation details for the convention's opening session, and information on bus passes for delegates, alternates, and press. The report also lists available medical personnel for the delegation, announces a Chicago bus tour, and includes a calendar of women's events such as receptions and luncheons featuring political figures and supporters.